Munazarah Beretika: Perbandingan Pemikiran Al-Ghazali dan Fatwa MUI - Muhammad Alfi Fakhri; Mutammimah Mutammimah; Siti Herlina zr; Siti Nuri Nurhaidah; Ahmad Irfan (Lembaga Pengembangan Kinerja Dosen, 2026)
Degradation of religious discourse on social media platforms—characterized by flame wars, takfir accusations, hate speech, and ad hominem attacks that trigger horizontal conflicts—highlights the urgent need to re-examine the ethics of munāẓarah (scholarly debate). This study aims to analyze Al-Ghazali’s concept of munāẓarah in Kitab Ayyuhal Walad and the Indonesian Council of Ulema’s (MUI) perspective on public debate ethics, examine their convergences and divergences, and formulate an applicable contemporary digital munāẓarah framework. Utilizing a qualitative library research approach with content and comparative analysis, the study reveals that while Al-Ghazali focuses on micro-ethical spiritual control (muraqabah al-nafs) to prevent heart diseases, MUI emphasizes macro-ethical civic literacy (jidal bi al-lati hiya ahsan) for public enlightenment. Moving beyond static theoretical comparison, this research synthesizes both perspectives into a practical output: The Four Digital Munāẓarah Ethics, comprising Digital Intention Audit, Data Validation and Anti-Ad Hominem, Civil Communication and Takfir-Free, and Exit Strategy. This framework serves as a practical guideline for dai, netizens, and the public to foster healthy and constructive religious discussions in the digital sphere.